Process engineering - Ahmed Mohamed Farid Shaaban; Azza Ibrahim Hafez; Mona Amin Abdel-Fatah; Nabil Mahmoud Abdel-Monem; Mohamed Hanafy Mahmoud (Egyptian Journal of Petroleum)
A nanofiltration (NF) based separation process is used to treat the effluent from a textile plant to allow for water reuse and fulfill environmental standards. The wastewater effluent contains reactive black (RB5)- and disperse (DR60) dyes. A NF-unit model E2 series with HL 2521 TF spiral wound module was used to carry out experiments. 90 & 93% color removal and COD reduction for RB5 and 98 & 95% for DR60 were achieved. A parametric study of the separation process is undertaken to characterize the effects of the operating variables, e.g., trans-membrane pressure, dye/salt concentration in the feed, temperature, and cross flow velocity. The solution diffusion model was used to develop power correlations to calculate the permeate side solute mass transfer coefficient as a function of effective cross-flow Reynolds number. In contrast to the commonly assumed constant hydraulic solvent permeability, a non-linear relationship was developed over the applied trans-membrane net driving pressure. The latter correlates exponentially with salt permeability for both dyes. The effects of feed salt-content on solute mass transfer coefficient, water and salt permeability, concentration polarization, dye hydrophobicity and ionic strength were studied. Results were used to assess engineering specifications of a commercial size NF-plant (500 m3/d capacity).